An equation for tacrolimus daily dose calculation in renal transplant patients - simple and cost saving? - Rančić Nemanja; Lozanov-Crvenković Zagorka; Mikov Momir; Vavić Neven; Dragojević-Simić Viktorija (Vojnosanitetski Pregled, 2018)
nema